1986
DOI: 10.1542/peds.78.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Constipation and Meconium Ileus Equivalent in Patients With Cystic Fibrosis

Abstract: Constipation and its complications, particularly meconium ileus equivalent, may become management problems in patients with cystic fibrosis. The medical records of 168 patients with cystic fibrosis were reviewed for the prevalence of constipation and meconium ileus equivalent. Of 168 patients, 54 (32%) had experienced at least one episode of constipation which responded to oral or rectal laxative therapy. In 16 of the study group (9%) meconium ileus equivalent developed. Patients younger than 5 years of age ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…As per the literature, the prevalence of constipation in children and adolescents with CF ranges from 32% to 57% (1)(2)(3)(4)(5)(6)(7). This considerable variability, at least in part, is because studies have used different diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…As per the literature, the prevalence of constipation in children and adolescents with CF ranges from 32% to 57% (1)(2)(3)(4)(5)(6)(7). This considerable variability, at least in part, is because studies have used different diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that 43 out of 105 (41%) CF patients between 6 and 21 years of age had, according to the ESPGHAN criteria, symptoms of constipation, with relief of these problems after the initiation of laxatives, which, as pointed out above, is an essential component of these criteria. The higher point prevalence in this study might be due to the age of the patients included, as opposed to the 0-18 year group in the article by van der Doef [5] , as it is known that, although constipation can be present in this younger age group, it is more rare [2] . The article by Stefano [7] also once again highlights the differences between constipation in CF and non-CF patients, with the vast majority (86%) of constipated CF patients having a normal frequency of bowel movements (i.e.…”
Section: Journal Of Cystic Fibrosismentioning
confidence: 59%
“…The actual period prevalence, i.e. having or ever having had symptoms of constipation, varied from 32% −57% [2][3][4][5] . So far the ESPGHAN criteria were used in only two studies.…”
Section: Journal Of Cystic Fibrosismentioning
confidence: 99%
“…Data about constipation prevalence in CF patients were compiled in eight scientific publications. However, only two of these articles 13 , 14 determined constipation prevalence as their main objective. In the other studies, constipation frequency was gathered along with the prevalence of other gastrointestinal manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant causes of this divergence are apparently the different definitions adopted, the diverging objectives, and the varying eligibility criteria to include the cases. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%